Effects of a semester-long massage practice on low back pain and physical fitness in university students. - Erzeybek, Mustafa Said; Kaya, Fatih; Eynur, Baybars Recep; Eynur, Aytül; Onen, Mert Eray (Journal of Bodywork & Movement Therapies, 2025)
This quasi-experimental study aimed to investigate the effects of a semester-long massage practice on low back pain and physical fitness among university students. A total of 124 students (87 male, 37 female) enrolled in a sports science program participated in structured massage training using the Albert Hoffa technique. Over a 14-week period, students practiced three times per week under supervision. Physical activity was assessed using the short-form International Physical Activity Questionnaire (IPAQ), and back pain was measured using the Oswestry Disability Index (ODI). Findings indicated a significant moderate negative correlation between physical activity and low back pain levels (r = −.62, p <.001), with moderate to large effect sizes observed across outcomes. These results demonstrate that semester-long educational massage interventions can enhance physical activity, reduce musculoskeletal pain, and may represent a promising, non-pharmacological strategy for managing musculoskeletal complaints in young adults. Future research should extend to clinical populations, employ longer follow-up periods, and incorporate standardized protocols to strengthen generalizability. • A semester-long massage training improved students' physical activity levels. • Low back pain and disability scores significantly decreased after the intervention. • Moderate negative correlation found between IPAQ and ODI scores. • Massage education shows promise as a non-pharmacological strategy for young adults.